375 SINGLE DOSE ORAL DEXAMETHASONE IN THE EMERGENCY MANAGEMENT OF CHILDREN WITH EXACERBATION OF MILD TO MODERATE ASTHMA. (1st January 2005) - Altamimi, S.; Robertson, G.; Jastaniah, W.; Davey, A.; Dehghani, N.; Chen, R.; Colbourne, Leung K. M.
Abstract : Objective: To compare the efficacy of single dose oral dexamethasone with five days of twice daily prednisolone in the management of mild to moderate asthma exacerbation in children. Methods: A prospective, randomized, double blinded trial of children 2 to 16 years of age who presented to the emergency department with acute mild to moderate asthma exacerbations. Subjects received single dose oral dexamethasone (0.6mg/kg to a maximum of 18mg) or five days of twice daily oral prednisolone (1mg/kg/dose to a maximum of 30mg). After discharge, subjects were called in 48 hours to assess progress, and re-evaluated in five days. Results: Baseline characteristics were comparable in the Dex group (n=67, mean age= 60 months), and in the Pred group (n=67, mean age= 48.5months). When Dex was compared to Pred, during the first visit mean time to discharge was 210 minutes vs. 258 minutes (mean difference -48 minutes, CI: -108, 12) and admission rate was 6(9%) vs. 9(13.4%). Two subjects from the Pred group dropped out of the study due to repeated vomiting. For subjects discharged home (61 vs. 56), the admission rate after initial discharge was 3(4.9%) vs. 1(1.8%). The mean number of days needed for Patient Self Assessment score to return to baseline (0-0.5) was 5.21vs 5.22 (mean difference 0.01, CI -0.70, 0.68). Conclusion: In children with mild to moderate asthma exacerbation, a single dose of oral dexamethasone (0.6 mg/kg) is safe and efficacious, when compared to five days of oral prednisolone.